Mobilisasi Oleh Elit Tradisional Pada Pemilihan Kepala Daerah Tahun 2018 Di Kabupaten Kerinci - Santri Utami Pajri; Indah Adi Putri; Zainal Arifin (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Elections are held periodically, namely once every five years, with the aim of a constitutional change of power as regulated in the 1945 Constitution (UUD 1945). General elections are held in the form of presidential elections, regional head elections and legislative elections. At this time political parties are no longer the only force in political contestation. Elections that take place at the local election level still often encounter interference from elites, especially traditional elites, such as the regional elections that occurred in Kerinci Regency, where one of the elite's roles is as a force in mobilizing the masses. Many candidates use traditional culture to get more supporters in the election. Through its mass power, it can be used as an effective political machine in political contestation. This confirms that political mobilization is the key to winning election contestations. In analyzing mass mobilization by traditional elites, researchers use mobilization theory according to Stefano Bartolini and elite theory from Pareto and Mosca because mobilization in politics is a series of processes carried out by traditional elites in recruiting participants to obtain special support in an election. This research uses a qualitative approach with an instrumental case study method. The research results show that mass mobilization was commanded by traditional elites, such as the Depati and Ninik Mamak of Kerinci Regency, who directed and ordered the community and their nephews to choose certain agreed candidate pairs. The order was issued by Depati Ninik Mamak in a joint meeting to decide on support for candidate pair Adirozal-Ami Taher, so that the results of the meeting resulted in a joint agreement to win the pair Adirozal-Ami Taher.